A Scenario for Origin of Global 4 mHz Oscillations in Solar Corona - Li Xue; Chengliang Jiao; Lixin Zhang (Universe)
We establish a spherically symmetric model of solar atmosphere, which consists of the whole chromosphere and low corona below the <semantics>1.25</semantics> solar radius. It is a hydrodynamic model with heating in the chromosphere through an artificial energy flux. We performed a series of simulations with our model and found oscillations with a peak frequency of ∼4 <semantics>mHz</semantics> in the power spectrum. We confirmed that this resulted from the p-mode excited in the transition region and amplified in a resonant cavity situated in the height range ∼<semantics>4×103</semantics>–<semantics>2×104</semantics> km. This result is consistent with global observations of Alfvénic waves in corona and can naturally explain the observational ubiquity of <semantics>4<mspace width="2pt"></mspace>mHz</semantics> without the difficulty of the p-mode passing through the acoustic-damping chromosphere. We also confirmed that acoustic shock waves alone cannot heat the corona to the observed temperature, and found mass upflows in the height range ∼<semantics>7×103</semantics>–<semantics>7×104</semantics> km in our model, which pumped the dense and cool plasma into the corona and might be the mass supplier for solar prominences.